1978
DOI: 10.1001/jama.1978.03280350066018
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Thyroid Disorders in Connecticut

Abstract: A prospective study involving 1,544 patients who had annual physical examinations during a one-year period was conducted to determine the incidence of htyroid abnormalities in a practice of general internal medicine. A total of 5.8% abnormalities were found including nodular disease, thyroiditis, Graves' disease, hypothyroidism, simple goiter, and iatrogenic hyperthyroidism. No thyroid cancer was detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
2
1

Year Published

1980
1980
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 5 publications
0
6
2
1
Order By: Relevance
“…The prevalence of morphological abnormalities of the thyroid gland in the general population [22,23] is much lower than that found in our study of patients who received mantle irradiation. Brander et al [24] found thyroid nodules in 35% of healthy females with an average age of 52 years.…”
Section: Discussioncontrasting
confidence: 85%
“…The prevalence of morphological abnormalities of the thyroid gland in the general population [22,23] is much lower than that found in our study of patients who received mantle irradiation. Brander et al [24] found thyroid nodules in 35% of healthy females with an average age of 52 years.…”
Section: Discussioncontrasting
confidence: 85%
“…Our prevalence rate is, however, a little lower compared to that of dos Remedios et al, namely 6.1/1000 females and 3.5/1000 males, which was estimated by screening clinic patients using free thyroxine index, 13 but similar to that of Baldwin and Rowett. 17 The prevalence rates in non-Saudis as compared to Saudis were lower in females but higher in males. This could be a reflection of the age and sex distribution of non-Saudis in the Kingdom as well as the diversity of their nationalities.…”
Section: Discussionmentioning
confidence: 95%
“…One pateint had a papillary carcinoma. The incidence of nodular thyroid abnormalities in MD appears to be increased as most studies suggest an incidence of between 2 and 5% in the general population (Vander et al, 1954(Vander et al, , 1968Sokal, 1959;Matovinovic et al, 1965, Pincus et al, 1967Tunbridge et al, 1977;Baldwin & Rowett, 1978). Postmortem studies have shown abnormal thyroid glands in MD patients with atrophic changes, cellular infiltrates or increased colloid formation being reported by Berthold (1958) in eleven out of thirty patients.…”
Section: Discussionmentioning
confidence: 98%